UTILIZATION OF RICE HUSK AS RAW MATERIAL IN SYNTHESIS OF MESOPOROUS SILICATES MCM-41 - Suyanta Suyanta; Agus Kuncaka (Universitas Gadjah Mada, 2011)
The research about synthesis and characterization of MCM-41 from rice husk has been done. Silica (SiO2) was extracted from rice husk by refluxing with 3M hydrochloric solution at 80 °C for 3 h. The acid-leached rice husk was filtered, washed, dried and calcined at 650 °C for 6 h lead the rough powder of rice husk silica with light brown in color. Characterization was carried out by X-ray diffraction (XRD) and FTIR spectroscopy method. Rice husk silica was dissolved into the sodium hydroxide solution leading to the solution of sodium silicate, and used as silica source for the synthesis of MCM-41. MCM-41 was synthesized by hydrothermal process to the mixture prepared from 29 g of distilled water, 8.67 g of cetyltrimethyl ammonium bromide (CTMAB), 9.31 g of sodium silicate solution, and amount mL of 1 M H2SO4. Hydrothermal process was carried out at 100 °C in a teflon-lined stainless steel autoclave heated in the oven for 36 h. The solid phase was filtered, then washed with deionised water, and dried in the oven at 100 °C for 2 h. The surfactant CTMAB was removed by calcination at 550 °C for 10 h with heating rate 2 °C/min. The as-synthesized and calcined crystals were characterized by using FTIR spectroscopy, X-ray diffraction and N2 physisorption methods. In order to investigate the effect of silica source, the same procedure was carried out by using pure sodium silicate as silica source. It was concluded that silica extracted from rice husk can be used as raw materials in the synthesis of MCM-41, there is no significant difference in crystallinity and pore properties when was compared to material produced from commercial sodium silicate.